The impact of management consultants on public service efficiency. (28th January 2019) - Kirkpatrick, Ian; Sturdy, Andrew J; Alvarado, Nuria Reguera; Blanco-Oliver, Antonio; Veronesi, Gianluca
Abstract : Public sector organisations often make use of management consultants in policy implementation, but we know little about the outcomes. The paper reports one of the first quantitative evaluations of the impact of consulting advice on efficiency of public sector organisations. We employ an extensive dataset covering English NHS acute care hospital trusts over a four-year period. Based on PCSEs estimations, the findings show a significantly positive relationship between consulting expenditure and organisational in efficiency. These results lend support to critical accounts of management consulting, highlighting the need for organisations to be circumspect in deciding whether and how to use these services.